2014
DOI: 10.1007/978-3-319-08506-7_6
|View full text |Cite
|
Sign up to set email alerts
|

C3P: Context-Aware Crowdsourced Cloud Privacy

Abstract: Abstract. Due to the abundance of attractive services available on the cloud, people are placing an increasing amount of their data online on different cloud platforms. However, given the recent large-scale attacks on users data, privacy has become an important issue. Ordinary users cannot be expected to manually specify which of their data is sensitive, or to take appropriate measures to protect such data. Furthermore, usually most people are not aware of the privacy risk that different shared data items can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The top priority for privacy preservation in crowdtesting is to protect user privacy in the data collection process. Harkous et al [56] found that users usually had difficulties in accessing the privacy levels of their shared data. A context-aware framework was proposed to identify the privacy risk of shared data on a cloud server.…”
Section: Crowdtestingmentioning
confidence: 99%
See 3 more Smart Citations
“…The top priority for privacy preservation in crowdtesting is to protect user privacy in the data collection process. Harkous et al [56] found that users usually had difficulties in accessing the privacy levels of their shared data. A context-aware framework was proposed to identify the privacy risk of shared data on a cloud server.…”
Section: Crowdtestingmentioning
confidence: 99%
“…The main limitation of their work is that the proposed system only identifies the risky data items without proposing solutions. Moreover, there is no policy or computational technique proposed in [56].…”
Section: Crowdtestingmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies [20,21,22] focus on security and privacy aspects which are major obstacles in cloud adoption for both individuals and companies. Previous work [21] proposed a semantic framework based on crowd-sourcing to determine the sensitivity of items and diverse attitudes of users towards privacy. Bohli et al [20] provide a survey for four different multicloud architectures with various security and privacy-enhancing designs.…”
Section: Spclusteringmentioning
confidence: 99%